CLDN6-specific CAR-T cells plus amplifying RNA vaccine in relapsed or refractory solid tumors: the phase 1 BNT211-01 trial - Mackensen, Andreas; Haanen, John B.A.G.; Koenecke, Christian; Alsdorf, Winfried; Wagner-Drouet, Eva; Borchmann, Peter; Heudobler, Daniel; Ferstl, Barbara; Klobuch, Sebastian; Bokemeyer, Carsten; Desuki, Alexander; Lüke, Florian; et al. (Nature medicine, 2023)
The oncofetal antigen Claudin 6 (CLDN6) is highly and specifically expressed in many solid tumors, and could be a promising treatment target. We report dose escalation results from the ongoing phase 1/2 BNT211-01 trial evaluating the safety and feasibility of chimeric antigen receptor (CAR) T cells targeting the CLDN6 with or without a CAR-T cell-amplifying RNA vaccine (CARVac) at two dose levels (DLs) in relapsed/refractory CLDN6-positive solid tumors. The primary endpoints were safety and tolerability, maximum tolerated dose and recommended phase 2 dose (RP2D). Secondary endpoints included objective response rate (ORR) and disease control rate. We observed manageable toxicity, with 10 out of 22 patients (46%) experiencing cytokine release syndrome including one grade 3 event and 1 out of 22 (5%) with grade 1 immune effector cell-associated neurotoxicity syndrome. Dose-limiting toxicities occurred in two patients at the higher DL, resolving without sequelae. CAR-T cell engraftment was robust, and the addition of CARVac was well tolerated. The unconfirmed ORR in 21 evaluable patients was 33% (7 of 21), including one complete response. The disease control rate was 67% (14 of 21), with stable disease in seven patients. Patients with germ cell tumors treated at the higher DL exhibited the highest response rate (ORR 57% (4 of 7)). The maximum tolerated dose and RP2D were not established as the trial has been amended to utilize an automated manufacturing process. A repeat of the dose escalation is ongoing and will identify a RP2D for pivotal trials. ClinicalTrials.gov Identifier: NCT04503278 . In the ongoing phase 1/2 BNT211-01 trial, CLDN6-specific chimeric antigen receptor (CAR)-T cells given with or without CARVac, a CAR-T cell-amplifying RNA vaccine, were well-tolerated and exhibited encouraging clinical activity in patients with relapsed or refractory CLDN6-positive solid tumors, with the highest response rate in patients with germ cell tumors.